2004
DOI: 10.2172/910630
|View full text |Cite
|
Sign up to set email alerts
|

Converting Simulated Sodium-bearing Waste into a Single Solid Waste Form by Evaporation: Laboratory- and Pilot-Scale Test Results on Recycling Evaporator Overheads

Abstract: Conversion of Idaho National Engineering and Environmental Laboratory radioactive sodium-bearing waste into a single solid waste form by evaporation was demonstrated in both flask-scale and pilot-scale agitated thin film evaporator tests. A sodium-bearing waste simulant was adjusted to represent an evaporator feed in which the acid from the distillate is concentrated, neutralized, and recycled back through the evaporator. The advantage to this flowsheet is that a single remote-handled transuranic waste form is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 1 publication
2
22
0
Order By: Relevance
“…No liquid was found in any of the drums (Griffith, 2004). Thus the risk of corrosion of canisters due to acidic liquids is very small.…”
Section: 442mentioning
confidence: 87%
See 4 more Smart Citations
“…No liquid was found in any of the drums (Griffith, 2004). Thus the risk of corrosion of canisters due to acidic liquids is very small.…”
Section: 442mentioning
confidence: 87%
“…The second and third series of pilot tests (Griffith, 2003b;Griffith, 2004) demonstrated that the fraction of feed evaporated, and hence the bottoms composition, correlated with the bottoms temperature. The bottoms temperature, and hence the product composition, can thus be controlled by controlling the steam pressure.…”
Section: 442mentioning
confidence: 99%
See 3 more Smart Citations